The Regulator-Regulatee Relationship in High-Hazard Industry Sectors New Actors and New Viewpoints in a Conservative Landscape - Le Coze, Jean-Christophe; Journé, Benoît (SpringerBriefs in Safety Management, 2024)
This open access book addresses relationships that develop from the complex set of legislative, regulatory, and institutional arrangements that arise in the governance of high-hazard industries, especially those connected with safety. It analyses the difference in practices between high-hazard sectors such as nuclear power, chemical processing, and transport with those in the finance and healthcare sectors. The relationship between regulating and regulated entities is important in ensuring that safety is not subordinated to other concerns and in maintaining public confidence. As a result, the brief addresses various pressures and trade-offs inherent in that relationship, trade-offs between such considerations as: cost of the oversight activity and its effectiveness; regulator independence and its level of competency and understanding of the risks involved; ability to provide advice on meeting regulatory goals and being able to criticize decisions made; and effectiveness and intrusion in operational activities. The contributors show how, over time, a more horizontal or "decentred" approach to regulatory oversight has appeared, with a larger degree of delegation of certain decisions to industry and a greater role for a range of third parties such as certification bodies, auditors, insurers, industry associations and NGOs. This book is of interest to academics working in the fields of safety science or organizational management and to practitioners, regulators and policy-makers concerned with health and safety and critical infrastructure.